Online Lending Business And Its Criminal Aspect Of Collectibility - Nalom Siagian; Hisar Siregar; Roida Nababan (Departement of Mathematics Education, 2023)
Online lending business opportunities or what is often referred to as fintech applications grow very fertile in today's digital era. On the one hand, it can be assumed as the growth of the economy, but on the other hand, the collectibility side for these business actors reflects a concerning reality. There are events where they are actually disturbing when collecting using harsh methods, with words that tend to be threatening and inhumane. This is an unlawful reality. This paper will discuss the criminal aspects of these activities from the perspective of the Electronic Information and Transaction Law. This study is conducted using a descriptive method with a normative approach. The data sources analyzed are secondary data, which are then interpreted qualitatively. The results of the study show how the billing model can be seen as an unlawful act in Article 27 Paragraph (1) of the Electronic Information and Transactions Law. Thus, the individual collectors of the online loan company can be held criminally liable.